DEVELOPMENT OF THE FOREIGN LANGUAGE TEACHER’S PROFESSIONAL COMPETENCE: MODERN CHALLENGES AND CONTINUOUS PROFESSIONAL GROWTH - Durdas , Alla; Harbuza , Tetiana; Radchenko, Yuliia; Starosta, Hanna; Holohudina , Yelyzaveta (Continuing Professional Education: Theory and Practice, 2025)
The article deals with professional competence as a key foundation for preparation and ongoing development of foreign language teachers at university. Attention has been drawn to the increasing complexity of teaching responsibilities in the modern era and it is stressed on the necessity for higher education pedagogues to remain open to rapidly developing educational contexts, technological innovations and various students’ expectations. The authors consider the issue of a foreign language teacher’s professional competence, including linguistic proficiency, pedagogical methodology, intercultural sensitivity, psychological awareness and digital literacy, which are essential for providing effective language education. Particular focus is placed on the difficulties educators face when striving to coordinate their professional development with contemporary international educational standards. These challenges include prioritizing of student-centered learning, promotion of communicative language use, advancement of inclusive teaching practices and the necessity of lifelong learning. The article discloses the specific competencies of modern university foreign language teachers, such as the integration of digital instruments in foreign language teaching, encouraging critical and intercultural thinking among students and the teachers’ ability to create flexible and approachable content of their courses. The study highlights various ways to continued professional growth, including participation in international collaboration, initiatives of academic exchange, virtual learning environments and institutional programs of efficiency growth. The article also reaffirms the importance of structured, reflective and continuous professional development in ensuring high quality of foreign language teaching in a global academic landscape. The study contributes to the conversation on improving foreign language teachers’ education and proposes the instruments and ways for building professional competence that are in line with the changing needs of modern university pedagogues and the challenges they face.